Association between heart rate-corrected QT interval and severe peripheral arterial disease in patients with type 2 diabetes and foot ulcers. Issue 8 (26th July 2021) - Hong, Jing; Liu, Wen-Yue; Hu, Xiang; Jiang, Fei-Fei; Xu, Ze-Ru; Li, Fang; Shen, Fei-Xia; Zhu, Hong
Abstract : Background: A prolonged heart rate-corrected QT interval (QTc) has been associated with peripheral artery disease (PAD) in the general population. However, no study to date has identified a link between prolonged QTc and the severity of PAD in patients with diabetes mellitus and foot ulcers (DFUs). This study aimed to investigate this relationship. Methods: This multicenter study enrolled 281 patients with DFUs. The severity of PAD was classified into no severe PAD group (without stenosis or occlusion) and severe PAD group (with stenosis or occlusion) based on duplex ultrasonography. The association of prolonged QTc with severe PAD was evaluated in a multivariable mixed-effect logistic regression model, with the hospital as a random effect. Directed acyclic graphs were used to drive the selection of variables to fit the regression model. Results: Patients with severe PAD had longer QTc than those without. Based on the multivariable mixed-effect logistic regression model, a prolonged QTc was positively associated with severe PAD (odds ratio (OR) = 2.61; 95% CI: 1.07–6.35) and severe DFUs (Wagner grade score ≥ 3) (OR = 2.87; 95% CI: 1.42–5.81). Conclusions: A prolonged QTc was associated with severe PAD in patients with DFUs. Further research is required to ascertain whether the association is causal.